Pengaruh Limbah Tulang Sapi sebagai Agregat Kasar dalam Beton Normal l - Damar Khusnan Najib; Destiana Safitri (Institut Teknologi Garut, 2025)
Concrete is a composite material made from several components, using the primary ingredients of cement, fine aggregates, coarse aggregates, air, and additional materials if needed, with a specific composition. This study aims to analyze the effect of using cattle bone waste as an additional material for coarse aggregates in normal concrete production. Cattle bone waste was chosen due to its abundant availability and the presence of hydroxyapatite minerals, which have the potential to enhance the strength of concrete. Variations of cattle bone mixture at 0%, 5%, 10%, and 15% were used in the production of cylindrical test specimens, followed by compressive strength testing after a 28-day curing process. The results of the tests show that the higher the percentage of cattle bone used, the lower the compressive strength of the concrete. Concrete without cattle bones (0%) had the highest compressive strength of 16.62 MPa, while concrete with 5%, 10%, and 15% mixtures had average compressive strengths of 14.58 MPa, 11.76 MPa, and 11.26 MPa, respectively. The decrease in compressive strength is due to the more porous and brittle physical properties of cattle bones compared to natural aggregates, which affects the density and strength of the concrete structure. Therefore, the use of cattle bones as an alternative aggregate should be limited to a certain level to maintain the quality of the concrete. This study contributes to reducing organic waste and innovating the use of local materials in environmentally friendly construction.